2023
DOI: 10.1177/20556683231163337
|View full text |Cite
|
Sign up to set email alerts
|

Beyond step counts: Including wear time in prosthesis use assessment for lower-limb amputation

Abstract: Introduction The purpose of this study was to test a novel activity monitor that tracks the time a prosthesis is worn, and the nature of the ambulatory activity conducted with the prosthesis. These capabilities allow prosthesis users’ wear and accommodation practices (e.g., temporary doffing) to be monitored, and the intensity of their activities to be assessed. Methods A portable limb-socket motion sensing system was used to monitor doffs, walk bouts (≥5 steps), low locomotion (2–4 steps), stationary position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Even for higher-activity prosthesis users, skin irritation and breakdown throughout the rehabilitation process can impede their return to activity by limiting time in their prosthetic socket. Prior work has shown that lower-extremity prosthesis users doffed their sockets several times over the course of the day likely owing to pain or discomfort or change their liners to limit unfavorable conditions within the socket, even when wearing their prosthesis from 12.8 to 18.8 hours a day ( DeGrasse et al, 2023 ). Finding a solution to prevent skin irritation and breakdown is paramount to continued success of all prosthesis users.…”
Section: Introductionmentioning
confidence: 99%
“…Even for higher-activity prosthesis users, skin irritation and breakdown throughout the rehabilitation process can impede their return to activity by limiting time in their prosthetic socket. Prior work has shown that lower-extremity prosthesis users doffed their sockets several times over the course of the day likely owing to pain or discomfort or change their liners to limit unfavorable conditions within the socket, even when wearing their prosthesis from 12.8 to 18.8 hours a day ( DeGrasse et al, 2023 ). Finding a solution to prevent skin irritation and breakdown is paramount to continued success of all prosthesis users.…”
Section: Introductionmentioning
confidence: 99%